1994
DOI: 10.1121/1.408639
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and sex on speech intonation and duration for matched statements and questions in French

Abstract: Intonation characteristics (mean F0, standard deviation of F0, and F0 difference) and speaker rate (duration) were assessed in 40 matched statement–question pairs produced by 40 normal adult speakers of Canadian French, similar to Eady and Cooper [J. Acoust. Soc. Am. 80, 402–415 (1986)] for American English. Subgroups were also compared by both sex (male versus female) and age (younger versus older subjects). Results revealed a greater difference in fundamental frequency between statement–question pairs than r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…In earlier work, which targeted the role of declination in speech processing, sentences were generally longer, and in a gating task the effect of declination was not observed until listeners heard the object in sentences of the type subject-auxiliary verb-object-verb (Van Heuven & Haan, 2002). Also, durational differences in declarative sentences pronounced as either question or statement were only found for longer SVO sentences (Van Heuven & Van Zanten, 2005; but see Ryalls et al, 1994). These results are in line with the assumption that the short utterances used in the present study may not have provided sufficient early prosodic information.…”
Section: General Discussion and Conclusionsupporting
confidence: 88%
“…In earlier work, which targeted the role of declination in speech processing, sentences were generally longer, and in a gating task the effect of declination was not observed until listeners heard the object in sentences of the type subject-auxiliary verb-object-verb (Van Heuven & Haan, 2002). Also, durational differences in declarative sentences pronounced as either question or statement were only found for longer SVO sentences (Van Heuven & Van Zanten, 2005; but see Ryalls et al, 1994). These results are in line with the assumption that the short utterances used in the present study may not have provided sufficient early prosodic information.…”
Section: General Discussion and Conclusionsupporting
confidence: 88%
“…For example, both neurologically impaired groups clearly distinguished interrogatives from declaratives in terms of intonation differences, albeit to a significantly less degree than normal control subjects. In a previous study, normal control subjects produced interrogative sentences at a significantly faster rate than declarative sentences [5]. In this study we also found that both neurologically impaired groups produced interrogatives at a faster rate than declaratives, despite an overall slower speech rate in ataxic speakers.…”
Section: Discussionsupporting
confidence: 63%
“…Such question-statement pairs offer a unique opportunity to investigate prosody in isolation from phonemic content. Eady and Cooper [4] found that normal speakers make a difference of 'at least 30 Hertz', and our research with normal speakers revealed on overall average difference of 78 Hz [5]. Such objective measures provide an opportunity to quantify the prosodic impairment of dysarthric patients.…”
Section: Introductionmentioning
confidence: 94%
“…1 An exhaustive combination of focus, modality, and emotion features yielded 24 prosodically unique exemplars of each item or 96 productions per speaker ͑2 itemsϫ2 lengthsϫ3 focus contextsϫ2 modalitiesϫ4 emotions͒. A recorded vignette preceded each trial to elicit tokens conveying specific combinations of prosodic attributes ͑Coo-per et al, 1985;Ryalls et al, 1994͒. Vignettes consisted of a question or short passage that biased the target response; half of the recordings biased a response with a statement intonation and half with a question intonation. Differences in focus were rendered by modifying the vignette to place information to be used contrastively as ''new'' or unresolved within the situational context ͑e.g., .…”
Section: B Materialsmentioning
confidence: 99%